EVALUASI SIFAT FISIKA TANAH TYPIC HAPLUDULTS PADA EMPAT GENERASI TANAM KELAPA SAWIT PT SOCFIN INDONESIA DI KEBUN AEK LOBA KABUPATEN ASAHAN - Sihombing, Edison Parulian Sihombing (Jurnal Online Pertanian Tropik, 2017)
Charges against oil palm plantations as the cause of soil degradation and as a ringleader of environmental damage, drought land and take nutrients in large quantities make this study important. The purpose of this study to determine the effect of oil palm cultivation on the four-generation of sustainable planting to changes in soil physical characteristics Typic hapludults. Description of soil profiles and sampling was conducted at four sites representing generations of planting oil palm. As the control mixed crop that has not been planted with oil palm. Soil samples tested in the laboratory for each of the characteristics of soil physics. Results showed oil palm cultivation in soil Typic hapludults for four generations of plants continuously unchanged physical characteristics significant level. This shows that the cultivation of oil palm trees in a sustainable manner with the best management practice systems PT Socfindo can maintain the physical characteristics of the soil.